Tomato Mi-gene Resistance-Breaking Populations of Meloidogyne Show Variable Reproduction on Susceptible and Resistant Crop Cultivars - Ploeg, A T (Journal of nematology, 2023)
© 2023 A. T. Ploeg et al., published by Sciendo.